Historiography of Hadith: The Development of the Hadith Writing Movement in the 2nd and 3rd Centuries AH - Muhammad Rifqy Farhanullah; Engkos Kosasih; Muhammad Al Mighwar (al-Afkar, Journal For Islamic Studies, 2025)
Hadith is a summary of the prophet's life journey which is a guide and guidance for Muslims. Hadith writing is thought to have existed since the time of the prophet and then continued its development during the time of the shahifahs. The development of hadith writing became increasingly rapid with codification starting in the second century Hijriah. This development continued in the 3rd century Hijriah, which is considered the glorious time of hadith writing. In these two centuries, monumental works in hadith literature were born, each of which had its own characteristics and format, structure and systematics, representing the writing of hadith in those two centuries. This article aims to reveal the development of the hadith writing movement in the second and third centuries of the Hijriah as well as the characteristics of hadith literature writing in those two centuries. This article uses the library research method by collecting and compiling data sourced from books, articles, scientific journals and papers. -other electronic papers.